Integration of OTSM-TRIZ and Analytic Hierarchy Process for Choosing the Right Solution. (2015) - Borgianni, Yuri; Frillici, Francesco Saverio; Rotini, Federico
Abstract: A relevant part of TRIZ literature concerns the steps of the problem solving process, hence the analysis of the troublesome situation, the identification of the core problem and its resolution. Conversely, few efforts have been dedicated to support the last phase of the conceptual design process, which regards the selection of the most promising solutions to be further developed. The lack within TRIZ of an instrument capable to fulfill the abovementioned task led the authors to investigate the classical decision making methods and their applicability in the context of selecting the most valuable concepts downstream of problem solving phases characterized by divergent thinking. Several potential approaches have been surveyed and, among the others, the Weighted Sum Method and the Analytic Hierarchy Process seem to hold some of the characteristics requested by an ideal method to facilitate the decision making. In this paper, both of them have been tested through a real case study in order to verify their actual applicability and to reveal strengths and weaknesses with a particular focus on their capability to guide the decision process when a plurality of parties (e.g. policy makers, domain experts) are involved. The testing activity revealed that the Analytic Hierarchy Process resulted overall more appreciated by the experimenters, thanks to the systematic approach employed to select the best solution among a sample of alternatives developed through the Network of Problems.